Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content1. The Degree to which Arabic Language Teachers in Saudi Arabia Possess Distance Learning CompetenciesMisfer Saud Mubarak Al-Hersh 2. The 21st Century Skills Included in family Education and Life Skills Course for the Secondary StageAmani Hashim Alzubaidi, Abeer Mohammed Alarfaj 3. The Degree of Availability of the Science, Technology, Society and Environment (STSE) approach in science curricula in the Sultanate of OmanHumood Sulieman Saif Al-Rumhi, Ahmed Humaid Mohammed Al-Badri 4. Using Inquiry Strategy in Teaching Social Studies to Develop Metacognitive Studies among Second Grade Intermediate StudentsNoier Hamdan Alghedani 5. The effectiveness of using simulation strategy in developing Arabic calligraphy skills for eighth grade students in the Capital MunicipalityAbdulkareem Ali Mohamed Al-Lahabi 6. The Reality of Continuous Evaluation in the English Language Course in the Elementary Stage in Saudi ArabiaMishal Abdullah Algosairi, Ahmad Hasan Albdour 7. Constructing an instrument to measure attitude towards distance learning and applying it to a sample of the students of Mu'tah UniversityNofah Sameh Kamel Al-Mawadeh, Hanin Lafi Zal Al-Mawadeh
Keywords: Journal of Curriculum and Teaching Methodology